The p53 gene family in vertebrates: Evolutionary considerations - Biscotti, Maria Assunta; Barucca, Marco; Carducci, Federica; Forconi, Mariko; Canapa, Adriana (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2019)
The origin of the p53 gene family predates multicellular life since TP53 members of this gene family have been found in unicellular eukaryotes. In invertebrates one or two genes attributable to a TP53‐like or TP63/73‐like gene are present. The radiation into three genes, TP53, TP63, and TP73, has been reported as a vertebrate invention. TP53 is considered the “guardian of the genome” given its role in protecting cells against the DNA damage and cellular stressors. TP63 and TP73 play a role in epithelial development and neurogenesis, respectively. The evolution of the p53 gene family has been the subject of considerable analyses even if several questions remain still open. In this study we addressed the evolutionary history of the p53 gene family in vertebrates performing an extended microsyntenic investigation coupled with a phylogenetic analysis, together with protein domain organization and structure assessment. On the basis of our results we discussed a possible evolutionary scenario according to which a TP53/63/73 ancestor form gave rise to the current TP53 and a TP63/73 form, which in turn independently duplicated into two genes in agnathe and gnathostome lineages. Research Highlights In vertebrates the p53 family is made up of three transcription factors, TP53, TP63, and TP73. The former is considered the “guardian of the genome” given its role in protecting cells against the DNA damage and cellular stressors. TP63 and TP73 play a role in epithelial development and neurogenesis, respectively. The presence of homologous sequences in unicellular eukaryotes indicates that the origin of the p53 gene family predates multicellular life. The split into three genes occurred in the vertebrate common ancestor. However several questions on the evolution of the p53 gene family still remain open. In this paper, a new intriguing evolutionary scenario for the p53 gene family is proposed on the basis of results obtained from an extended phylogenetic and microsyntenic analyses. According to our model a TP53/63/73 ancestor form gave risen to the current TP53 and a TP63/73 form, which in turn has been independently duplicated into two genes in agnathes and gnathostomes. A TP53/63/73 ancestor form gave rise to the current TP53 (probably lost in lamprey) and a TP63/73 form after a gene duplication event. Subsequently the current TP63 and TP73 genes duplicated from the TP63/73 gene independently in agnathes and gnathostomes.